Genetic characterisation of animal genetic resources for sustainable utilisation and development - Panandam, Jothi Malar (Universiti Putra Malaysia Press, 2012)
Farm animal genetic resources are not only a source of food and animal protein, but also play a multi-functional role providing other commodities and services. The vast array of breeds and species found across the world is the outcome of the effects of the environment over thousands of years and human activities. Over the last decades, however, this diversity has become threatened. Indigenous and local breeds, which are often more adapted to the local environmental conditions and management systems, require low maintenance and are less prone to diseases, have been either replaced by imported high yielding breeds or have their gene pool introgressed with genes from these breeds. The exotic breeds, which have been subjected to high intensity selective breeding, tend to have narrowed genetic base. Genetic diversity is crucial for animals to adapt to changing environmental conditions and to survive in the face of disease outbreaks. It is also the resource for improvement of livestock productivity to meet current and future demands. The loss of genetic diversity among animal genetic resources has caused global concern as it affects food security, trade and livelihood of farmers. With the need to arrest further genetic erosion, the Global Plan of Action for Animal Genetic Resources was developed by the Food and Agriculture Organisation of the United Nations (FAO). The first of the four strategic priorities areas focuses on characterisation, inventory and monitoring of trends and associated risks. The animal genetic resources of Malaysia comprise of the indigenous breeds, the local breeds, locally developed synthetic and composite breeds, traditional populations, commercial breeds and lines, and the introduced breeds. The indigenous and local breeds have been neglected in favour of imported breeds or have been indiscriminately crossed with other breeds resulting in non-descript crosses. Except for the recently developed synthetic breeds, many synthetic breeds developed in the past can no longer be found or suffer from admixture with genes from other breeds. We are rapidly losing our animal genetic resources. In addition to this the genetic diversity within the existing populations is fast eroding as a result of mismanagement of breeding activities and failure to keep proper records. Conservation and sustainable utilisation and development of animal genetic resources is only possible through genetic characterisation to identify unique qualities and to detect threats of inbreeding and hybridisation. Genetic characterisation is the evaluation of variation at the chromosomal or DNA level. It requires the assessment of genetic variability within and among populations, lines, breeds and species using molecular markers and specific genes. It may be used to explain population dynamics and migration patterns, and to identify inbreeding and admixture within livestock populations. It provides valuable information required for developing breeding strategies and genetic conservation strategies Association analysis using DNA markers and candidate genes may pave the path for use of marker-assisted selection (MAS) through early and accurate identification of animals with high breeding values and unique qualities. There are limited scientific studies evaluating the production and reproductive performances and genetic variability of local animal genetic resources. It is pertinent that the genetic structure of local animal genetic resources be evaluated and regularly monitored. Only then can our indigenous breeds, the locally developed synthetic breeds and non-descript crosses, and the introduced breeds besustainably developed to further enhance the local livestock industry and ensure food security in the future.